2007
DOI: 10.1186/1752-0509-1-49
|View full text |Cite
|
Sign up to set email alerts
|

Modeling protein network evolution under genome duplication and domain shuffling

Abstract: Background: Successive whole genome duplications have recently been firmly established in all major eukaryote kingdoms. Such exponential evolutionary processes must have largely contributed to shape the topology of protein-protein interaction (PPI) networks by outweighing, in particular, all time-linear network growths modeled so far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
1
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 87 publications
1
46
1
2
Order By: Relevance
“…For instance, there have been between two and four consecutive whole-genome duplications in all major eukaryote kingdoms in the past 300-500 MY (5). This actually amounts to a more-or-less similar contribution of new genes from whole-genome duplication as from individual gene duplications [i.e., one fixed event per 100-200 MY Ӎ 10 Ϫ3 fixed events per gene per MY, assuming a 10% fixation rate after a wholegenome duplication with Ϸ10,000 genes (5)]. …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, there have been between two and four consecutive whole-genome duplications in all major eukaryote kingdoms in the past 300-500 MY (5). This actually amounts to a more-or-less similar contribution of new genes from whole-genome duplication as from individual gene duplications [i.e., one fixed event per 100-200 MY Ӎ 10 Ϫ3 fixed events per gene per MY, assuming a 10% fixation rate after a wholegenome duplication with Ϸ10,000 genes (5)]. …”
mentioning
confidence: 99%
“…In fact, duplication-divergence events have occurred and continue to occur at a wide range of genomic scales, from many independent duplications of individual genes † [10 Ϫ3 fixed events per gene per million years (MY) (4)] to rare but evolutionary dramatic duplications of entire genomes [one fixed event per 100-200 MY (5)]. For instance, there have been between two and four consecutive whole-genome duplications in all major eukaryote kingdoms in the past 300-500 MY (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this, paralogous proteins present a conserved pattern of interactions and therefore share more partners than expected by chance [5]. Furthermore, networks modeled according to this duplication/ divergence idea display topological properties very similar to real biological networks [4,7,8]. Pereira-Leal et al [6] showed that duplication of self-interaction nodes is crucial for the evolution of more interconnected networks.…”
Section: Introductionmentioning
confidence: 81%
“…Although domain shuffling was not explicitly explored in their paper, their data is in accordance with a model in which domain shuffling is important in defining the topology of PPI networks. Evlampiev and Isambert [8] modeled the evolution of PPI networks under a scenario of genome duplication, followed by extensive domain shuffling. They concluded that evolved networks are robust to extensive domain shuffling.…”
Section: Domain Shuffling Goes Systems Biologymentioning
confidence: 99%